Isolation, molecular identification of lipid-producing Rhodotorula diobovata: optimization of lipid accumulation for biodiesel production - Mohamed E. Osman; Asharf Bakery Abdel-Razik; Khaled I. Zaki; Nesma Mamdouh; Heba El-Sayed (Journal of Genetic Engineering and Biotechnology, 2022)
Abstract Background The increased demand for oil and fats to satisfy the ever-increasing human needs has enhanced the research in this field. Single-cell oils or microbial lipids produced by oleaginous microorganisms are being utilized as an alternative to traditional oil sources. Oleaginous yeasts can accumulate lipids above 20% of their biomass when they are grown under controlled conditions. Results In the present study, sixty-five yeasts were isolated from different sources. Using Sudan Black B staining technique, five yeast isolates were selected. Under nitrogen-limited cultivation conditions, the Co1 isolate was the best lipid accumulation potential of 39.79%. Isolate (Co1) was characterized morphologically and identified using the ribosomal DNA internal transcribed spacers regions (rDNA-ITS) from their genomic DNA. The sequence alignment revealed a 99.2% similarity with Rhodotorula diobovata. Under the optimized conditions, Rhodotorula diobovata accumulated lipids up to 45.85% on a dry biomass basis. R. diobovata, when grown on different raw materials, accumulated lipid up to 46.68% on sugar beet molasses medium, and the lipid had a high degree of monounsaturated fatty acids which gives biodiesel better quality. Conclusions The data suggest that the potent oleaginous yeast, R. diobovata, together with the use of cheap feedstock raw materials such as sugar beet molasses, can be considered as a promising feedstock for biodiesel production.